Barriers and opportunities to accessing social support in the transition from community to prison: a qualitative interview study with incarcerated individuals in Northern Norway - Line Elisabeth Solbakken; Rolf Wynn (BMC Psychology, 2022)
Abstract Background Incarcerated individuals have poor mental health compared to the general population. Social support has a beneficial effect on mental health. The buffering model proposes that social support facilitates coping under stressful conditions, while the main effects model suggests that belonging to social networks and having positive social interactions are beneficial for mental health. Prisons are a highly interesting context for studying social support, as imprisonment is perceived as stressful and disrupts social relationships and the availability of support. This study aims to explore incarcerated individuals' perceptions of social support from various sources in the transition from community to prison, its perceived significance for mental health, and the opportunities and barriers to accessing social support in a Norwegian prison context. Methods The experiences of eight incarcerated individuals from a prison in Northern Norway were gathered through conducting individual in-depth interviews. The data analysis was inspired by Charmaz’s version of Grounded Theory. Results Social support from peers was perceived to be important for the well-being and preserving of mental health in prison. Support from informal sources outside prison and prison officers were not granted the same significance by the participants. Although prison life was perceived as stressful, social support in the form of companionship, the feeling of belonging, shared activities, and everyday conversations were more important for the participants than support focusing on coping with the stress of incarceration. Conclusions Peers are perceived to be the most important source of social support, and vital for well-being and mental health in prison. Barriers to support from family, friends and prison officers may amplify the significance of support from peers.